A STUDY OF INTRODUCTION TO COLLEGE ENGLISH TEACHERS’ BELIEFS IN THEIR TEACHING ROLES - Subekti, Adaninggar Septi (Sanata Dharma University Yogyakarta, 2019)
The study investigated Introduction to College English’s teachers’ beliefs about their roles as teachers. The participants of the study were thirteen teachers. It used their reflection papers as the source of data and secondary data, as the reflections were not originally written for the purpose of this study. The study used thematic analysis of the secondary data and it produced four themes or categories regarding the teacher participants’ beliefs about their roles. First, they believed they should design various activities that promoted learning. Secondly, they needed to monitor their students' progress and conduct appropriate assessments. They also believed that they should always have alternative plans whenever their original plans were not successful, and the last, they believed that they needed to show learners their attention and care. Based on the results of the study and the limitations, some suggestions for future studies are also presented. DOI: doi.org/10.24071/ijiet.2019.030103